(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
In this paper, we present an explanation for the problem of the abstract versions of Peter Wason’s four-card selection task: modest subjects’ results when they are confronted with these tasks. Our explanation poses that individuals do not comprehend the task rule as a conditional sentence, but as a biconditional one, causing that subjects do not choose the correct cards. Santamaría presented an objection for any approach that suggests a biconditional interpretation in the task selection. In this work, we discuss this objection based on the apparent primacy of a logical rule in human reasoning: modus ponens. Additionally, we present a study based on Socratic dialogue seminars with a tutorial style, developed by us, to check whether our explanation is viable or not, and discuss the results achieved.